(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As science and technology progresses, the world is changing all the time. The presence of technology now seems difficult to escape. It’s impossible to keep up with the incredible rate of change and development in ICT. Every one of these tools has been tried out in educational settings before. A great number of academics have taken use of mobile devices’ portability and accessibility in the digital age. These gadgets have a significant impact on the lives of their owners in a variety of ways. To date, digital technology development has been focused on social communication, and only a small number of people have seen m-learning as a primary educational activity at higher education institutions. An example of m-learning is using mobile devices such as smartphones, phablets, tablets, and netbooks to learn. Because students may learn anywhere and at any time with mobile learning, it’s more adaptable than e-learning. Since smartphones and other mobile devices are already common household items, m-learning has emerged as a significant new approach to education. It’s more engaging with more individuals, communication and collaboration with m-learning than with traditional learning. M-learning is casual, student-centered, self-directed, and collaborative. The usage of social media in education has advanced thanks to this new technology. Students are increasingly utilizing technology advancements to enhance their learning in order to achieve top academic results. When a student and teacher have a good working relationship, learning becomes enjoyable. Students will grasp a concept faster if the teacher presents it in the way they want. Most university students use their free time on social networks, mainly WhatsApp. It’s a natural fit for university students’ schedules.